GOFOOD AND GOJEK APP: FORM OF TRAVERSAL WORLD DOMINATION - Sri Kusuma Winahyu; Yumna Rasyid (IJLECR (International Journal of Language Education and Cultural Review), 2021)
Social life always presents endless discourse of phenomenon. In the era of the birth of Generation Z, also born the fact that traversal world has started to become a “new footing” in human life. Beginning with traditional text forms, multimodal text, and hypermodal texts, hypertext is now so massively developing in society. Without realizing, It is able to build power over its users. This power is reflected in layers of links that are read through hypertext semiotic classifications. This study discusses the hypertextualized Gojek online applications with their content, Gofood. This application is part or example of the traversal genre. The hypertext semiotic which was initiated by Lemke based on hypertext semantic analogy by Halliday, carried out at the first discussion stage. Furthermore, data analysis was carried out using Fairclough's critical discourse analysis as a transdisciplinary analysis stage in the second discussion. The results of the study show that the form of dominance of the power of this online application that can be seen from the meaning of its semiotic classification, namely presentational, orientational, and organizational. Meanwhile, the relationship that appears from the application with social life clearly shows that the traversal world has dominated and control the lives of today's people.